From Programmer to Composer: A Survey of Creative Authorship in the Age of AI - Balighi, Ali (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação Musical, 2025)
This article explores the transformation of musical authorship in the age of artificial intelligence, reframing the composer as a mediator between code, sound, and agency. Drawing from perspectives in composition, programming, philosophy, music theory, and technological design, the paper examines how AI systems redistribute creative labor and challenge traditional models of authorship. Through analytical reflection and case studies, it argues for a posthuman, systemic understanding of composition one grounded in ethical design, cultural responsibility, and technological transparency. Rather than displacing the human composer, AI invites a redefinition of authorship as collaborative, distributed, and evolving.